Scenario-Based Dialogues and Performance-Based Assessment for Early Arabic Kalam: Implementing a Communicative Approach in an Islamic Elementary School - Faidatul Baroro; Moh. Hilbal Hisan Al Gholi (Lingu, 2026)
Purpose – This study investigates how a communicative approach—operationalised as Scenario-Based Dialogues and performance-based assessment—was implemented in fourth- and fifth-grade Arabic kalam materials at Islamic Elementary School (SDI) Annuriyah Rambipuji.. Design/methods/approach – Using a qualitative descriptive case-study design, data were collected through systematic document analysis of teaching modules, semi-structured interviews with the Arabic teacher and head of madrasah, and classroom observations triangulated by thematic analysis. Findings – Findings show a substantive curricular shift from grammar-centred tasks to functionally oriented scenario dialogues, multimodal scaffolds, and a semesterly “Kalam Performance Week” that privileges fluency and interactional competence. Classroom evidence indicates increased vocal participation and emergent linguistic confidence during guided tasks, although persistent code-switching outside lessons and a shortage of authentic child-appropriate Arabic resources constrained wider language habituation. The study concludes that contextually relevant scenario tasks and performance assessment can meaningfully foster early communicative competence, but sustainable impact requires teacher training, accessible authentic materials, and out-of-class habituation strategies. Limitations include the single-site case design and lack of longitudinal retention measures, which restrict generalisability and call for multi-site, mixed-method, and longitudinal follow-up studies to test scalability and durability. Research Implications – Practical recommendations include targeted in-service training on interactive facilitation, development or procurement of age-appropriate Arabic materials, and structured school routines to extend classroom speaking into broader communicative ecologies.